Pengaruh Pola Asuh Orang Tua Authoritative Terhadap Kematangan Emosi Mahasiswa Universitas Muhammadiyah Malang - Okta Viana Nanda Pactica; Mitah Khaerunisa; Putri Ragil Dwiyanti; Shafa Camila Oktania (Elsia: Jurnal Psikologi Manusia, 2024)
The relationship with parents and the parenting style applied are important aspects of a child's psychological development. One type of parenting style is authoritative parenting, which is an upbringing that is supportive and responsive to children, but still provides boundaries in the form of firm behavior towards children. Good levels happiness and emotional maturity can also result from good parenting and upbringing from their parents. Emotional maturity itself is a condition characterized by the ability to control and control one's emotions in various situations. This study aims to see the influence of authoritative parenting styl on emotional maturity. Sampling in this study using purposive sampling with a sample of 164 people at the University of Muhammadiyah Malang. Data collection was carried out using two scales, namely authoritative parenting and emotional maturity, then the resulting data was analyzed using simple linear regression analysis. Based on the results of linear regression analysis, it can be seen that there is a significa influence between authoritative parenting and emotion maturity. The result showed that the research hypothesis was accepted with a p-value <.001 (p <0.05).